Mechanics of Soft Materials - Volokh, Konstantin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book provides a concise introduction to soft matter modelling. It offers an up-to-date review of continuum mechanical description of soft and biological materials from the basics to the latest scientific materials. It includes multi-physics descriptions, such as chemo-, thermo-, electro- mechanical coupling. It derives from a graduate course at Technion that has been established in recent years. It presents original explanations for some standard materials and features elaborated examples on all topics throughout the text. PowerPoint lecture notes can be provided to instructors. .
Tensors -- Kinematics -- Balance laws -- Isotropic elasticity -- Anisotropic elasticity -- Viscoelasticity -- Chemo-mechanical coupling -- Electro-mechanical coupling.
Keywords: Mechanics, Applied; Solids; Soft condensed matter; Biomaterials; Solid Mechanics; Soft and Granular Matter; Biomaterials